Factors affecting solidification of hazardous waste materials - Phontong Sujiwatthana; Shin, H. S.; Chongrak Polprasert; Samorn Muttamara; French Government (Bangkok : Asian Institute of Technology, 1987)
A cement-silica based technique, one of the solidification processes was studied for waste stabilization. Experiments were conducted in laboratory with four types of hazardous wastes including cadmium (Cd), lead (Pb), aldrin (AD) and chlordane (OHM). Effects of several factors on leachability and compressive strength of solidified mixture were investigated. Portland cement was used to mix with the waste for solidification. The factors studied were the amount of hazardous waste added, water/cement ratio, surface area/volume ratio, pH of extract solution and curing time of solidified samples . Samples were extracted with acidified solution following the extraction procedure. The amount of hazardous waste in leachate was found proportional to the initial amount of waste in a solidified sample. Increase of surface area/volume ratio of solidified sample or decrease in pH of extract solution increased the amount of leached waste. Increase of curing time did not much affect the amount of leached waste but increased the compressive strength mostly until 28 days. When the water/cement ratio was 0.5, amount of leached waste was the least but the sample had the most compressive strength. Also the greatest compressive strength was obtained when the l east amount of hazardous waste was added. Maximum allowable amount of waste to be added in solidification was estimated by modelling techniques . Also the treatment cost per unit we ight of waste was calculated for practical application.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Salvage (Waste, etc.)